Radiation situation in the forest fund territory: radioactive contamination monitoring results - Karbanovitch, Larisa (Journal of the Belarusian State University. Ecology, 2026)
On the territory of the forest fund of the Ministry of Forestry, which was subjected to radioactive contamination as a result of the Chernobyl accident, a set of protective measures is being implemented to comply with the norms and rules for ensuring radiation safety. Forestry activities are regulated taking into account indicators of the radiation situation: the soil contamination density with cesium-137 (137Cs) (hereinafter – contamination density), the gamma radiation dose rate, and the content levels of 137Cs in forest products [1].The control of radioactive contamination is an integral part of organizational and technical protective measures and provides operational information for making organizational decisions in forestry. Information on radiation situation indicators is constantly updated during radiation surveys of forest fund lands, logging sites, and radiation control of forest products – wood (commercial wood and firewood), wild berries, mushrooms, birch sap, and honey.The results of the radiation survey are used to classify forest blocks into radioactive contamination zones and for conducting logging, provided that normatively clean timber is obtained. Radiation control of forest products is carried out to determine the compliance of the 137Cs radionuclide content with permissible (reference) levels and to define the directions of wood use (round timber, fuel wood).A decrease in the area of radioactive contamination of the forest fund is established annually. In 2025, compared to 2024, the area decreased by 13.8 thousand ha, or by 1.15%; over the past 5 years – by 48.1 thousand ha (3.89%); and over 10 years – by 187.1 thousand ha (13.6%). The area of forests with high contamination density (15 Ci/km² or more) has decreased since 2021 by 14.7 thousand hectares, or by 16.2%. As the contamination density decreases, the gamma radiation dose rate decreases by up to 2.0% per year.According to the results of radiation monitoring of forest products, an excess of permissible levels of 137Cs content in commercial timber is established in up to 2.0% of cases per year, and in forest food products – in up to 40% of cases, with the largest share of samples exceeding the norms found in mushrooms and wild berries.To date, with sufficient reliability, the content levels of 137Cs in wood within forest blocks and taxation units classified as radioactive contamination zones are known. Obtaining information about the 137Cs content in wood for the current period and in the forecast for a given date, including visualization on a map, is provided by the functions of the specialized information system “Radioactive Contamination of Forests ‘RadFor’”.Positive changes in the radiation situation in forests, a significant amount of information on the results of monitoring radioactive contamination of the forest fund and forest products, accumulated experience, and the use of modern data storage and processing technologies can be used to optimize protective measures in the long-term period after the accident.
Keywords: forestry; protective measures; radioactive contamination; forest fund; forest products; radiation monitoring; reference levels